Reduction of Aflatoxin M1 Levels during Ethiopian Traditional Fermented Milk (Ergo) Production - Tsige Shigute; Alemayehu P. Washe (Journal of Food Quality)
In this study, the reduction of aflatoxin M1 (AFM1) levels during lab-scale ergo production was investigated through determination of the residual levels of AFM1 using Enzyme Linked Immunosorbent Assay. The results showed gradual and incubation time dependent reduction of AFM1 level in the raw milk samples being fermented to ergo. The maximum reductions of 57.33 and 54.04% were recorded in AFM1 in natural and LAB inoculums initiated fermentations, respectively, in 5 days of incubation. Although a significant difference (P=0.05) in the AFM1 decrease in the two types of fermentations was recorded, such findings could vary with milk samples depending on initial load of the microorganisms as determined by hygienic conditions. However, the level of AFM1 in control (sterilized) samples showed only a 5.5% decrease during the entire period of incubation. Microbiological investigation showed increasing LAB counts with incubation time. A gradual decrease in pH of the milk samples was observed during fermentation. Considering the fact that both viable and dead bacterial cells could remove AFM1 during ergo production, the mechanism is proposed as predominantly involving noncovalent binding of the toxin with the chemical components of the bacterial cell wall.